Relationship between uric acid levels and cardiometabolic findings in a large cohort of β-thalassemia major patients. (April 2018) - Vassalle, Cristina; Meloni, Antonella; Pistoia, Laura; Gamberini, Maria Rita; Spasiano, Anna; Gerardi, Calogera; Zuccarelli, Angelo; Casini, Tommaso; Righi, Riccardo; Missere, Massimiliano; Positano, Vincenzo; Ndreu, Rudina; et al.
Aim: to evaluate the relationship between uric acid (UA), hepatic and cardiac iron overload (T2*-MRI), ferritin, endocrinological diseases and cardiac complications in a large thalassemia major (TM) cohort.Methods:  A total of 369 TM patients (187 men; 33 ± 6 years) were retrospectively studied, from the myocardial iron overload in thalassemia (MIOT) electronic databank.Results: Multiple regression model identified male sex (p < 0.001), BMI (p < 0.001) and T2* (p ≤ 0.001) as UA independent correlates. Moreover, UA and derivatives of reactive oxygen species (an oxidative index; r = -0.3; p ≤ 0.05) are inversely correlated. Conversely, the multivariate logistic analysis identified low UA (NANHES-III criteria) as one independent predictor for low global heart T2* (p < 0.5) together with liver iron concentrations (>3 mg/g/dw), heart failure, endocrinopathies, ferritin (>2000 ng/l), alanine transaminase (>40 UI/l) and/or aspartate transaminase (>35 UI/l) and/or glutamyl transferase (>64 UI/l).Discussion: UA appears directly associated to T2* and inversely with derivatives of reactive oxygen species, and as such reduced according to increased oxidative stress and cardiac iron overload in TM patients.